STAT3 exerts pro-tumor and anti-autophagy roles in cervical cancer - Lin Wu; Bowen Shen; Junpeng Li; Huirong Zhang; Ke Zhang; Yao Yang; Zhenyu Zu; Dongxiang Shen; Min Luo (BMC, 2022)
Abstract Background STAT3 plays an important role in cervical cancer. LC3B, the most potential molecular biomarker of autophagy that may promote or inhibit cancer progression, can be downregulated by STAT3. However the role of STAT3 in the autophagy of cervical cancer remains unclear. Purpose This study aimed to evaluate the relationship between STAT3 and LC3B in protein level, and verify whether STAT3 promotes proliferation, migration and plate colony formation by inhibiting autophagy of cervical cancer cells through bcl2-beclin1 axis. Results STAT3 was overexpressed in cervical cancer tissues, and negatively correlated with the expression level of LC3B. STAT3 knockout or knockdown significantly increased the autophagy level and decreased proliferation, migration, plate colony formation and subcutaneous tumorigenesis of cervical cancer cells in vitro and in vivo. STAT3 is known to mediate autophagy through Bcl2-Beclin1 complex. Bcl2 was positively whereas Beclin1 negatively correlated with STAT3 expression, indicating that Bcl2-Beclin1 complex involved in this transition. Conclusion STAT3 may upregulate the autophagy level of cervical cancer cells through the Bcl2-Beclin1 axis. This indicates that STAT3 may be an important prognostic and therapeutic target for cervical cancer.